Pengaruh Elemen Fraud Hexagon Theory Terhadap Fraud Laporan Keuangan - Suci Oktavia; Asniati Bahari; Rayna Kartika (Akuntansi & Ekonomika, 2022)
Financial statement fraud is a deliberate of misstatement on the financial report of a company or the omission of amounts or misdisclosures in financial statements to deceive financial statement users. This study aims to analyze the effect of elements of the fraud hexagon theory on financial statement fraud. Hexagon fraud has several elements, namely stimulus, capability, opportunity, rationalization, arrogance, and collusion. The results showed that the stimulus in terms of financial stability, the stimulus assessed from external pressure, and ego had an effect on fraudulent financial statements. The stimulus in terms of financial targets, capability assessed from the change of directors, opportunity or ineffective supervision on financial performance monitoring, rationalization, and collusion have no effect on fraudulent financial statements.